Evaluation of indoor residential satisfaction of the older adults in old residential areas: a case study of Sichuan, China - Siqi Yang; Taoping Bai; Zhongyou Li; Lin Feng; Jialu Zhang; Wentao Jiang (Journal of Asian Architecture and Building Engineering)
Based on the housing perceptions of older adults in China, this article sought to identify the factors affecting indoor residential satisfaction (IRS) in old neighborhoods. Although China is promoting healthy ageing in place, a comprehensive system of evaluation of indoor indicators remains to be fully established. Following the social research, we identified the main factors affecting healthy ageing in indoor residence. Fourteen influencing factors were identified and categorised into four dimensions. Furthermore, necessary condition analysis was combined with regression analysis, a novel analytical approach that improves the accuracy of causal relationship interpretation. The survey assesses urban residents aged (60+), determining potential challenges when aging at home. Analysis of 394 valid questionnaires revealed four factors that affect the living experience of the older adults: “safety perception”, “daily activities”, “environmental comfort”, and “ageing-friendly facilities”, listed in descending order of scores. The characteristics of older people, including sex, age, health condition, and family status, were not only associated with a tendency towards IRS but also with higher requirements in the four dimensions. A safe indoor environment is a prerequisite for age-friendly homes. Popularising the concept of healthy ageing is urgent to enhance satisfaction compared with the upgrading of indoor facilities.